Scoping review on procurement and contractual risks affecting PPP housing construction project in Malaysia - Putri Zulaiha, Razi; Mohammad Idris, Ali; Noram Irwan, Ramli (AIP Publishing, 2023)
PPPs have been increasingly used in many countries as an alternative approach for the procurement of public facilities and services. Tendering periods in PPP project is significant since it represents a substantial ratio of overall project life-cycle principally the on-time and on-budget of the project. This paper conducted a scoping review in identifying the risk factors involved for the procurement and contractual risks in PPP housing construction projects. Five (5) risk factors that revolved on the procurement and contractual risk of PPP housing construction project. Among the identified risks are absence of transparency and accountability, absence of good governance, poor contract design, lack experience and knowledge of PPP mechanism, and insufficient capacity in procurement and negotiations. The obtained risk factors will act as a basis for further works on developing a risk management model that complementing the risk management plan.